Leukocyte‐associated Ig‐like receptor‐1 is a novel inhibitory receptor for surfactant protein D. Issue 1 (28th February 2014) - Olde Nordkamp, Marloes J. M.; van Eijk, Martin; Urbanus, Rolf T.; Bont, Louis; Haagsman, Henk P.; Meyaard, Linde
Abstract : Inhibitory LAIR‐1 as a novel receptor for SP‐D, and may mediate immunomodulatory effects of SP‐D. Abstract : The collagenous C‐type lectin, SP‐D, is a multitrimeric glycoprotein present at mucosal surfaces and is involved in host defense against infections in mammals. SP‐D has immunomodulatory properties, but the underlying mechanisms are incompletely understood. SP‐D contains collagen domains. LAIR‐1 is an inhibitory immune receptor at the cell surface of various immune‐competent cells that binds collagen. We hypothesized that the immunomodulatory functions of SP‐D can be mediated via interactions between its collagen domain and LAIR‐1. Binding assays show that SP‐D interacts via its collagenous domain with LAIR‐1 and the related LAIR‐2. This does not affect the mannan‐binding capacities of SP‐D, which induces cross‐linking of LAIR‐1 in a cellular reporter assay. Functional assays show that SP‐D inhibits the production of FcαR‐mediated reactive oxygen via LAIR‐1. Our studies indicate that SP‐D is a functional ligand of the immune inhibitory receptor LAIR‐1. Thus, we have identified a novel pathway for the immunomodulatory functions of SP‐D mediated via binding of its collagenous domains to LAIR‐1. This may provide a mechanism for the unexplained immunomodulatory function of the collagenous domains of SP‐D.